2019
DOI: 10.1111/sum.12526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the hydrolysis characteristics of three polyphosphates and their effects on soil phosphorus and micronutrient availability

Abstract: Polyphosphate is an alternative phosphorus (P) source which can substitute for orthophosphate‐based P fertilizers in agriculture. In order to explore the effects of polyphosphate addition on soil P availability, and how pH and temperature affect polyphosphate hydrolysis, an aqueous and a soil incubation experiment were conducted at different pHs (5.0 and 8.2) and temperatures (15, 25 and 35°C); the influence of polyphosphate addition on soil available micronutrients (i.e., iron—Fe, manganese—Mn and zinc—Zn) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…These differences between P fertilizer forms can be explained by the impact of soil water content on the availability of P in soil. Under drought conditions, available P from the Ortho-P fertilizer is expected to be higher than that of the Poly-P since the hydrolysis of Poly-P is greatly reduced under water stress conditions 47 , 48 . Similar results were found by Sekiya and Yano 46 , who reported that an increase in superphosphate (which are Ortho-P fertilizer) application rate improved cowpea stomatal density under different water supply conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These differences between P fertilizer forms can be explained by the impact of soil water content on the availability of P in soil. Under drought conditions, available P from the Ortho-P fertilizer is expected to be higher than that of the Poly-P since the hydrolysis of Poly-P is greatly reduced under water stress conditions 47 , 48 . Similar results were found by Sekiya and Yano 46 , who reported that an increase in superphosphate (which are Ortho-P fertilizer) application rate improved cowpea stomatal density under different water supply conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons may likely attributed to: (і) poly-P fertilizers belong to slow-release fertilizer, they move in condensed form in soil before it be hydrolyzed (McBeath et al, 2007), and it hardly interacted with soil mineral particles of Fe 2 O 3 /Al 2 O 3 (Hamilton, Hilger & Peak, 2016;Hamilton et al, 2018); (іі) poly-P may mobilize soil native P via chelating 2007) showed that poly-P activated recalcitrant oxidation forms of soil P (Fe 2 O 3 and MnO 2 ). Similarly, Wang et al (2019) found that poly-P fertilizer treatment significantly increased P availability in calcareous soil. Besides, poly-P fertilizer application decrease soil rhizosphere pH value at 0.1-0.5 unit (Hamilton et al, 2018;Rahmatullah, Wissemeier & Steffens, 2006;McBeath et al, 2007;Du et al, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…In this way, McBeath et al (2007) showed that poly-P activated recalcitrant oxidation forms of soil P (Fe 2 O 3 and MnO 2 ). Similarly, Wang et al (2019) found that poly-P fertilizer treatment significantly increased P availability in calcareous soil. Besides, poly-P fertilizer application decrease soil rhizosphere pH value at 0.1–0.5 unit ( Hamilton et al, 2018 ; Rahmatullah, Wissemeier & Steffens, 2006 ; McBeath et al, 2007 ; Du et al, 2013 ).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, increasing the dose of P-application decreased significantly Zn contents in both shoots and grains. This might occur because of Zn precipitation in soil in the form of zinc phosphate (Wang et al 2019). In presence of humic acid, significant increases occurred in concentrations of Zn in shoots and grains, especially in presence of the highest application level of humic acid (4 kg ha -1 ).…”
Section: -Seed Weightmentioning
confidence: 99%
“…starch, sweeteners, oil, beverages, glue, industrial alcohol, and fuel ethanol (Ranum et al 2014). Growing maize plants in calcareous soils requires adequate supply of phosphorus inputs (Leytem et al 2011), yet excessive P applications may affect negatively micronutrient availability in such soils (Sims and Pierzynski, 2005), including Zn (Wang et al 2019), consequently lessen their uptake by plants (Zhang et al 2012). Another negative aspect of using P-fertilizers in calcareous soils is that these soluble P-fertilizers are of low use efficiency because P-inputs undergo rapid immobilization (Bindraban et al 2020) through adsorption on the calcite surface (Izhar Shafi et al 2020).…”
Section: Introductionmentioning
confidence: 99%